Influence of IL-18 and IL-10 Polymorphisms on Tacrolimus Elimination in Chinese Lung Transplant Patients. (26th January 2017) - Zhang, Xiaoqing; Xu, Jiandong; Fan, Junwei; Zhang, Tao; Li, Yuping; Xie, Boxiong; Zhang, Wei; Lin, Shengtao; Ye, Ling; Liu, Yuan; Jiang, Gening
Abstract : Aims. The influence of interleukin-10 (IL-10) and interleukin-18 (IL-18) polymorphisms on tacrolimus pharmacokinetics had been described in liver and kidney transplantation. The expression of cytokines varied in different kinds of transplantation. The influence of IL-10 and IL-18 genetic polymorphisms on the pharmacokinetic parameters of tacrolimus remains unclear in lung transplantation. Methods. 51 lung transplant patients at Shanghai Pulmonary Hospital were included. IL-18 polymorphisms (rs5744247 and rs1946518), IL-10 polymorphisms (rs1800896, rs1800872, and rs3021097), and CYP3A5 rs776746 were genotyped. Dose-adjusted trough blood concentrations ( C/D ratio, mg/kg body weight) in lung transplant patients during the first 4 postoperative weeks were calculated. Results . IL-18 rs5744247 allele C and rs1946518 allele A were associated with fast tacrolimus metabolism. Combined analysis showed that the numbers of low IL-18 mRNA expression alleles had positive correlation with tacrolimus C/D ratios in lung transplant recipients. The influence of IL-18 polymorphisms on tacrolimus C/D ratios was observed in CYP3A5 expresser recipients, but not in CYP3A5 nonexpresser recipients. No clinical significance of tacrolimus C/D ratios difference of IL-10 polymorphisms was found in our data. Conclusions. IL-18 polymorphisms may influence tacrolimus elimination in lung transplantation patients.